The prevalence of hydronephrosis on ultrasound imaging in women with cervical cancer in Mankweng Hospital, Limpopo Province - Khosa, Refiloe Johana (My University, 2024)
Introduction Cervical cancer is the leading cause of cancer mortality in females particularly in sub-Saharan Africa and the fourth most frequently diagnosed malignancy globally. In 2020 cervical cancer was responsible for 5870 deaths in South Africa. Hydronephrosis is a frequent urological complication of advanced cancer of the cervix, with a prevalence of between 21.2% and 43.7%. The aim of the study was to evaluate the prevalence of hydronephrosis in women with cervical cancer diagnosed through trans-abdominal ultrasound at Mankweng Tertiary Hospital, Limpopo, South Africa. Methods A retrospective record-based analysis was conducted in the Radiology Department of Mankweng Hospital. Patients with histologically diagnosed cervical cancer who underwent trans-abdominal staging ultrasound between 01 July 2019 and 31 December 2019 were included. Data on patient age, parity, source of income, area of residence, size of the cervical lesion and the ultrasound imaging findings were extracted. Data was analysed using STATA v15. Descriptive statistics such as frequency and percentages were used to summarise all variables. Association between hydronephrosis and independent variables was evaluated using the Fisher’s exact score. Statistical significance was set at p-value <0.05. Results Two hundred patient records were evaluated. The patients’ age ranged from 27 to 89 years with the majority (68.4%, n=136) of the women aged between 31 - 60 years, and 28.5% (n=57) being older than 60 years. The majority of the women presented with a large tumour of >4cm (72.5%, n=143). Eighty-five patients had hydronephrosis (prevalence rate =42.5%), which was either bilateral (68.2%), or unilateral (31.8%). Tumour size was strongly associated with the occurrence of hydronephrosis. Other ultrasound findings were urinary bladder wall infiltration (13%, n=26), liver metastasis (3%, n=6), para-aortic lymph nodes involvement (1%, 2), and vesico-vaginal fistula (0.5%, n=1).Conclusion Hydronephrosis was the most frequent urological complication in advanced cancer of the cervix on ultrasound imaging, and was associated with a tumour size of >4cm.
Thesis (M.Med. (Diagnostic Radiology)) -- University of Limpopo, 2024
Keywords: Prevalence; Cervical cancer; Hydronephrosis; Ultrasound; Hydronephrosis; Cervix uteri -- Cancer; Generative organs, Female -- Cancer -- Imaging; Cancer -- Ultrasonic imaging